Northwest history. Mining. Mines reopened. 1926-01-22 (1926)
Days to resume on beaver creek. - It is believed the Day interests are preparing to resume work in the Amazon-Manhattan property on Beaver creek in the Coeur d'Alenes, which has been idle for some time. The property is worked through the Ray-Jefferson and when it was formerly operated it is understood to have developed a large body of ore, but because it was largely zinc it could not be shipped profitably at that time.